Caracterización socio económica y productiva de la parroquia rural Joséguango Bajo del cantón Latacunga, provincia de Cotopaxi 2022. - Iza Yugcha, Erika Gabriela (2022)
This research project aimed to do socio-economic and productive characterizations in "Joséguango Bajo" rural parish in Latacunga canton from Cotopaxi province. Surveys with different indicators were applied to know inhabitants' lives and the way of production. The results were that there isn't an intervention to improve the socio-economic and productive conditions of the sector under study. In the characteristics of the population, the gender does not vary significantly, where the family nuclei are three to four people, most families with at two children and an older adult per dwelling. Disability is not a significant problem of the parish but exists; the economic activity that they perform with higher percentages is Agriculture; the population has production areas where they qualify that their land is moderately productive, which are used for raising animals and crops, the products obtained are used for consumption and sale, 131 people were surveyed who are dairy farmers and most of them deliver their production to "piqueros" (milk collectors in trucks). The diagnosis shows that the population has different problems that should be solved with programs and projects.